2009
DOI: 10.1590/s1517-83822009000300016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the sterilization efficacy of domestic electric drills used in orthopaedic surgeries

Abstract: It is estimated that electric drills (ED) have been used in orthopaedic surgeries for bone drilling for more than 50 years in Brazilian hospitals. It is an electric, thermosensitive equipment, not indicated for surgical use, which has not been previously evaluated regarding the sterilization efficacy, being suspect of infection risk. This study evaluated the efficacy of sterilization by ethylene oxide (EtO) of new drills that were intentionally contaminated with Bacillus atrophaeus spores. An experimental, lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…They confirmed that this process is safe and effective in sanitizing and reusing electric drills. 5 We housed our drill in a formalin chamber because Taylor and Barbeito demonstrated formaldehyde gas thoroughly decontaminated laboratory chambers and scientific instruments in 1969. The source of this gas was paraformaldehyde powder.…”
Section: Discussionmentioning
confidence: 99%
“…They confirmed that this process is safe and effective in sanitizing and reusing electric drills. 5 We housed our drill in a formalin chamber because Taylor and Barbeito demonstrated formaldehyde gas thoroughly decontaminated laboratory chambers and scientific instruments in 1969. The source of this gas was paraformaldehyde powder.…”
Section: Discussionmentioning
confidence: 99%
“…Os PPS de uso único também foram objeto de estudo da autora e de seus colaboradores, que desenvolveram uma proposta para cálculo de custo do processamento de pinças descartáveis utilizadas em cirurgias videolaparoscópicas, instrumentalizando o gestor para a tomada de decisão do reúso desses produtos tendo em vista a questão econômica (Artigos 13 e 14) 13,14 . Três pesquisas comprovaram a possibilidade de esterilização de canetas de bisturi, lâminas de esternotomia e instrumentais laparoscópios, todos de uso único (Artigos 15, 16 e 19) 15,16,19 , suscitando questionamentos acerca dos critérios utilizados pelos fabricantes quanto ao rótulo de uso único de produtos registrados na ANVISA.…”
Section: Rev Sobecc 2008unclassified
“…The percentage of sporulated microorganisms was determined from slides prepared by the Gram staining method and by the Wirtz-Conklin method (Demidova and Hamblin, 2005;Golveia et al, 2009;Hamouda et al, 2002). The number of spores was determined in duplicate by manually counting 1000 spores and vegetative cells observed on the slides.…”
Section: Spore Preparation and Countmentioning
confidence: 99%